Synthesis and characterization of zeolite obtained from Toraja natural montmorillonite - Taba Paulina; Fauziah St.; Natzir Hasnah; Soekamto Nunuk H.; Sarungallo Rosalia S.; Nahru Nur W.; Astuti Yuli; Amin Ida I. (Journal of the Serbian Chemical Society, 2025)
Zeolites are an alternative material for treating heavy metal-containing waste. Synthetic zeolites exhibit excellent purity and particle size uniformity, which has led many researchers to explore their synthesis, including the use of natural minerals. This work aims to synthesize zeolites using the hydrothermal method with aluminosilicate sources from Toraja natural minerals. Toraja natural minerals, primarily composed of montmorillonite, hydrothermally react with NaOH at varying concentrations to form analcime (ANA) and cancrinite (CAN) zeolites. In the research we also examined the reaction time for zeolite formation. X-ray diffraction (XRD) analysis revealed that ANA and CAN exhibit tetragonal and hexagonal crystal structures, respectively. The Si/Al mole ratios were determined to be 2.40 for ANA and 1.27 for CAN, based on EDX analysis. The Fourier transform infrared (FTIR) spectra exhibit typical absorption bands within the spectral region of 700–400 cm-1, with increasing intensity observed at higher NaOH concentrations. ANA zeolite displays distinctive spectral features below 650 cm-1, attributed to double-ring vibrations in its structure. In contrast, triplet bands at 676, 622 and 565 cm-1 in the synthesized materials confirm the characteristic structure of cancrinite. SEM analysis revealed trapezium-shaped analcime crystals with an average size of 24 μm and rod-shaped cancrinite crystals with a length of 1.66 μm. Toraja minerals, particularly montmorillonite, contain secondary building units that form different zeolites depending on reaction conditions.